Integrating Amorphophalus Of Bukit Barisan Selatan National Park Into Problem-Based Learning to Foster Higher-Order Tinkhing Skills and Responsibility - Wisnu Juli Wiono (Phenomenon : Jurnal Pendidikan MIPA, 2025)
This study was conducted to determine the effect of integration of amorphophallus diversity in BBSNP on biodiversity material in a problem-based learning model on high-level thinking skills and responsibility of male and female students. The research design applied a pretest-posttest non-equivalent control group. The research sample was determined by applying the ANOVA consistency test and selected class X.1 (experimental) and class X.2 (control) from a population of 7 classes. The research instrument was in the form of a high-level thinking skills test and a responsibility questionnaire with a likert scale. The results of data analysis showed a sig. value for the model of 0.000 which is smaller than 0.05. This means that the application of PBL-integrated amorphophallus diversity BBSNP has a significant effect on students' critical thinking skills. Meanwhile, the sig. value for gender shows a figure of 0.964 ˃ 0.05 which means there is no difference in learning outcomes between male and female students. Analysis of the responsibility questionnaire shows that both males and females have an average responsibility score in the good category, namely 77.41 and 76.88. This finding indicates that the integration of local biodiversity in biology learning has a significant influence on improving specific learning outcomes.